Strategi Pengembangan UMKM Industri Kerajinan Pasca Covid 19 di Kabupaten Buton - Harjoprawiro, La; Mirosea, Nitri; Basri, Asriyani Mulia (LPPM Universitas BSI, 2024)
The craft industry is the activity of processing raw materials into semi-finished materials or semi-finished goods. The craft industry studied focuses on the typical Buton woven sarong industry, which is one of the MSME affected by Covid-19 in Buton Regency. The aim of this research is to determine and analyze the strengths and weaknesses as well as threats and opportunities of the Buton woven cloth craft industry. The samples used were 30 typical Buton woven cloth craft MSME. This research was analyzed using SWOT analysis. SWOT analysis can produce several alternatives that can be developed after Covid 19 so that they can develop and adapt to the business environment. The results of the research show that the MSME business in the Buton woven cloth craft industry has a strength of 2.06, a weakness of 0.82, an opportunity of 1.67, and a threat of 0.94. In the SWOT analysis diagram, the craft industry is in quadrant I position so that it has strengths and opportunities. Novelty in this research is a strategy used after Covid-19, namely strengthening creative craft branding through multimedia and social media.